Organologi dan Fungsi Bedug Produksi Sanggar Kembang Tanjung - Fauzi, Rafi Rizq; Permana, Rian; Rizal, Syamsul (Journal of Music Science, Technology, and Industry, 2025)
Purpose: This research focuses on making "Bedug musical instruments and the function of the Bedug music Sanggar Kembang Tanjung". The main objective of this research is to find out how to make Bedug musical instruments and the function of drum music at the Kembang Tanjung Studio. Research methods: Qualitative research was used to explore the physical and non-physical aspects of the drum. Data was collected through observation of the production and performance process, interviews with experts, craftsmen and studio members, and documentation in the form of notes, photos and recordings. Result and discussion: In the process of making the Sanggar Kembang Tanjung Bedug, the choice of materials is very important, where the wood used is coconut wood and mahogany wood, while the leather used is buffalo skin. The manufacturing process begins by forming the Bedug frame into a large tube using a tool called dodos to reach a diameter of 40-50 cm. After that, the process of smoothing the surface of the drum enters. The final stage involves installing hoops and drum skin and tied using slap rope and reinforced with drum buttons. Implication: This research shows that some of the functions of the drum musical instrument at the Tanjung Flower Studio include music as a means of entertainment, music as a cultural balance and music as a means of integrating society.